An exploration of the assessment for English (compulsory) at the Secondary School Certificate Examination of Dhaka Board - Islam, Mohammad Aminul (BRAC University, 2010)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master of Development Studies, 2008.